2012
DOI: 10.1103/physrevd.86.104027
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation for inspiraling eccentric compact binaries including pericenter precession

Abstract: Inspiraling supermassive black hole binary systems with high orbital eccentricity are important sources for space-based gravitational wave (GW) observatories like the Laser Interferometer Space Antenna (LISA). Eccentricity adds orbital harmonics to the Fourier-transform of the GW signal and relativistic pericenter precession leads to a three-way splitting of each harmonic peak. We study the parameter estimation accuracy for such waveforms with different initial eccentricity using the Fisher matrix method and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 81 publications
0
50
0
Order By: Relevance
“…Hence the spinless particle in the stationary gravitational field can not overcome the speed of light. Then the same is true in general case (46), at least for the metric which is sufficiently slowly varied in time.…”
Section: Three-dimensional Acceleration and Maximum Speed Of A Particmentioning
confidence: 59%
See 1 more Smart Citation
“…Hence the spinless particle in the stationary gravitational field can not overcome the speed of light. Then the same is true in general case (46), at least for the metric which is sufficiently slowly varied in time.…”
Section: Three-dimensional Acceleration and Maximum Speed Of A Particmentioning
confidence: 59%
“…This gives us the necessary tool for discussion of a fast moving body. The behavior of ultrarelativistic particles turns out to be important for analysis of near horizon geometry of extremal black holes (see [39]) and for accurate accounting of the corresponding corrections to geodesic motion near black hole [40][41][42][43][44][45][46][47][48].…”
Section: Three-dimensional Acceleration and Speed Of Light In Generalmentioning
confidence: 99%
“…The time-dependent waveform is computed with the help of Fourier-Bessel method in Ref. [12] and the waveform in Fourier space for arbitrary eccentricity was given in Ref [13].…”
Section: Introductionmentioning
confidence: 99%
“…But on the contrary, if ones can localize the gravitational wave source accurately through gravitational wave detection, the multi-messenger astronomy will benefit much [16]. For space-based detector-LISA, the authors in [17] found that higher eccentricity does increase the accuracy of source localization. It is interesting to ask how about ground-based detectors.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the source location accuracy, the sky position solid angle is [46] ∆Ω = 2π (∆ cos θ∆φ) 2 − ∆ cos θ∆φ 2 .…”
Section: Gravitational Wave Source Localization Accuracy Estimatmentioning
confidence: 99%